Vladimir Nabokov, un exemple d’aliénation créatrice - Marie Bouchet (Revue LISA)
The terms “strange” and “stranger” derive from extraneus, a Latin word literally meaning “outside of”. This article proposes to examine the notions of distance and limit which shape the consciousness of a foreigner / outsider—Vladimir Nabokov. Nabokov lost his native land when he was 18, and was condemned to remain a stranger in a foreign land. In his fiction, many “estranged” characters are to be found, especially as main focalizers or first-person narrators. The present article thus demonstrates how the concept of frontier is crucial to interpreting such alien status: these characters are forever estranged, due to geographical borders, temporal distances or linguistic barriers. Nabokov, himself a trilingual writer, challenged the very idea of a foreign language. His English, which he claimed was merely “second rate”, is indeed quite different from the style of American classics, yet it has a unique poetic flavor. Maybe because he “did not think in any language, but in images”, his condition as a foreigner was not felt as alienating. Contrary to most of his characters, hybridization seems to have been a powerful element inspiring his artistic impulse, as illustrated in his extraordinary linguistic virtuosity and his constant playing on words. Similarly, the repeated inclusion of other semiotic codes (painting, photography, advertisements,…) shows that by playing with limits and the interpenetration of familiar and strange(r) elements, Nabokov found a creative alternative to the usually alienating condition of being a foreigner.